Effect of endovascular management and anticoagulation alone on acute deep venous thrombosis in patients with inferior vena cava thrombosis - Lei Sun; Tao Yang; Huimin Xu; Wenpei Zhang (Scientific Reports)
Abstract This retrospective analysis assesses the effectiveness and safety of pharmacomechanical thrombectomy (PMT) and join CDT (catheter-directed thrombolysis) compared to CDT and with standard anticoagulation therapy for LEDVT (acute lower extremity deep vein thrombosis) with concomitant IVCT (inferior vena cava thrombosis). From January 2014 to January 2020, a total of 114 patients were diagnosed with acute LEDVT and IVCT at Shanxi Bethune Hospital. Patients were separated into three groups: PMT ± CDT (n = 77; 25 in this group also received CDT), CDT ± catheter thrombectomy (CDT ± CT) (n = 21), and conservative management (n = 16). The following outcomes were evaluated using SPSS: thrombus clearance rates, immediate clinical remission, and limb circumference decrease in the patients. The severity of post-thrombotic syndrome (PTS) and venous patency was evaluated at 1-year and 2-year follow-ups. Our findings showed that the PMT ± CDT group had significantly greater rates of immediate clinical remission and thrombus clearance compared with CDT ± CT and conservative treatment. PMT ± CDT achieved a thrombolysis rate of 74.5%, while the CDT ± CT group had a rate of 47.2% (p < 0.001). No method of treatment significantly reduced the overall rate of post-thrombotic syndrome (PTS) (p = 0.301). However, PMT ± CDT had a significantly lower PTS severity than CDT ± CT (p = 0.023). Overall, venous patency scores were significantly better in the PMT ± CDT group at 1-year and 2-year follow-up time points. The results of this study suggest that PMT ± CDT was significantly better than CDT ± CT, as well as conservative management of patients with LEDVT and IVCT concerning both short-term and long-term outcomes. The findings further support a preference towards endovenous management as a treatment approach in clinical practice for patients with such complications.